Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages rights enlarged. A weekly payment of 35/- for a married man who was perhaps receiving £5 to £10 per week is little better than starvation. For an injured workman who has to drag on weeks or months or years on such a payment it is bound to produce misery and demoralization. The benefits are, of course, grossly inadequate. Special Regulations It often happens that workers taking up some question affecting safety or health are told that there is no provision in the Factories Act covering the matter. This is natural because new processes are constantly being developed, and new substances (such as solvents) used, which may affect health or safety in unforeseen ways. The Minister of Labour has almost unlimited power, however, to extend the Factories Act by means of Special Regulations. Under Section 38 of the Act he can make special safety regulations for any factory where it appears necessary in view of the number and nature of the accidents occurring; and under Section 60 he can in the same way extend the regulations that safeguard the health of workers engaged in unhealthy processes. Workers must not, therefore, be put off easily by glib statements that such and such a process is perfectly safe, or that such and such a mishap was "just an accident." If they have reason to suspect that some job in their factory is harmful to the health or safety of the workers engaged on it, their best course is for the trade union organization to approach the management and the Factory Inspector and ask for special investigation to be made, so that any possible safety devices or health safeguards can be made compulsory by special regulation. 4. HOURS OF WORK. The workers to-day are pledged to expend all their energies to produce more and more for war needs. At first sight it may appear that the most obvious way to do this is to work longer hours each day, to work all seven days in the week, and to take no holidays. But it has been found by repeated experiment that very long hours as a regular practice do not give increased production, but lead to an increase in accidents and sickness and a lower rate of output. Thus the Ministry of Labour recommends a regular working week of not more than 60 hours for men and 55 for women as 23 21/2049